Wykorzystanie miar finansowych do zarządzania portfelem projektów innowacyjnych - Golej, Robert; Paszko, Piotr (Using Financial Measures in Portfolio Management of Innovative Projects, 2005)
The innovations management can use several methods. Very important is a portfolio management of new projects. It postulates the imperativeness of projects rating. It should base on, among other things, financial criteria. The article presents several techniques of innovative projects evaluation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 122-134